COMPARATIVE ANALYSIS OF CHICKPEA VARIETIES AND LINES UNDER DROUGHT AND HIGH TEMPERATURE CONDITIONS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article highlights the importance of chickpea (Cicer arietinum L.) in agriculture and food security, as well as the relevance of developing stable, high-yielding varieties under climate change and drought conditions. Within the framework of the study, 13 chickpea varieties and lines introduced from the international organization ICARDA were comparatively evaluated with local varieties Zumrad and Polvon. The adaptability of varieties and lines to local soil and climatic conditions, growth and development characteristics, phenological stages, morpho-biological traits, and resistance to high temperature, drought, diseases, and pests were assessed in demonstration nurseries. In addition, yield, thousand-seed weight, grain quality, and technological characteristics were determined. Based on the obtained results, high-yielding, stable varieties and lines with valuable agronomic traits were recommended as promising initial breeding material.
Keywords: Chickpea, grain legumes, breeding, ICARDA, varieties and lines, adaptability, yield, drought tolerance, heat tolerance, resistance to diseases and pests, soil and climatic conditions, food security.